HUBUNGAN POLA MAKAN DAN AKTIVITAS FISIK DENGAN PENGENDALIAN KADAR GULA DARAH PADA PENDERITA DIABETES MELITUS TIPE II DI WILAYAH KERJA PUSKESMAS KTK KOTA SOLOK - Netty Herawati; Kurniati Maya Sari WD (Ensiklopedia Social Review, 2021)
Controlling blood sugar levels is the main goal of nursing interventions that will be carried out in Diabetes Mellitus patients. Patients with diabetes mellitus are advised to always have a healthy lifestyle every day. Control blood sugar in DM patients by regulating diet such as: regulating the amount of food, type of food and frequency of eating hours and doing activities (sports). Non-Communicable Diseases (PTM), including Diabetes Mellitus, has now become a serious threat to global health. Quoted from WHO 2016 data, 70% of the world's total deaths and more than half of the disease burden. 90-95% of diabetes cases. Type 2 diabetes, which is largely preventable because it is caused by an unhealthy lifestyle. (Ministry of Health, 2018). Solok City has cases of Diabetes mellitus sufferers in four Puskesmas where there are 284 KTK Puskesmas working areas, while the number of visits to Type II Diabetes mellitus sufferers in the KTK Puskesmas work area is 50 people. Based on the results of research that has been carried out in the Working Area of the KTK Kota Solok Health Center, it was found that more than part (66%) of the respondents 'blood sugar levels were abnormal (high), more than part (64%) of the respondents' diet was not appropriate and more than some (60 %) respondents do not do physical activity regularly. There is a relationship between a diet that is not in accordance with abnormal blood sugar levels and there is a relationship that does not do physical activity with abnormal (high) blood sugar levels in the Working Area of the KTK Kota Solok Health Center. It is hoped that health workers will remind people with Type II Diabetes Mellitus, about the importance of dietary regulation in controlling blood sugar levels and carrying out regular physical activity (exercise) so that it can help in controlling blood sugar levels so that blood sugar levels can be controlled.